CD4 T cell depletion increases memory differentiation of endogenous and CAR T cells and enhances the efficacy of Super2 and IL-33-armored CAR T cells against solid tumors - Chrystal Paulos; Mary Jo Turk; Megen C Wittling; Yina H Huang; Asmaa O Mohamed; David Tyler Boone; Shannon L Ferry; Melanie C Peck; Alicia M Santos; Haille E Soderholm (Journal for ImmunoTherapy of Cancer)
Background Responsiveness to chimeric antigen receptor (CAR) T cell therapy correlates with CAR T cell expansion and persistence in vivo. Multiple strategies improve persistence by increasing stem-like properties or sustaining CAR T cell activity with combination therapies. Here, we describe the intrinsic ability of CAR T cells to differentiate into memory T cells, the effect of cytokine armoring, and neoadjuvant CD4 depletion therapy on CAR and tumor-specific endogenous memory T cells.Methods TRP1-specific or NKG2D CAR T cells alone or with Super2+IL-33 (S233) armoring and/or CD4 depletion were evaluated in immunocompetent B16F10 melanoma or MC38 colon cell carcinoma models without preconditioning. We characterized CAR and endogenous tumor-specific memory T cell precursors, establishment of circulating (TCIRC) and resident (TRM) memory T cell subsets, and ability to protect against secondary tumors.Results TRP1-specific or NKG2D CAR T cells had no effect on primary tumor growth in immunocompetent mice unless they were combined with S233 armoring or CD4 depletion. Unarmored CAR T cells expressed a stem-like phenotype in the tumor-draining lymph node and differentiated into CAR TCIRC memory cells in lymphoid organs and CAR TRM cells in the skin. In contrast, S233-armored CAR T cells exhibited an activated effector phenotype and differentiated inefficiently into CAR effector and central memory T cells. Combining CD4 therapy with unarmored CAR T cells increased CAR TCIRC and TRM memory T cells. Either CD4 depletion therapy or S233-armored CAR T cells induced activation of tumor-specific endogenous T cells that differentiated into both TCIRC and TRM memory T cells. CD4 depletion and S233-armored CAR T cell combination therapy synergized to increase endogenous memory T cells.Conclusions Unarmored TRP-1-specific or NKG2D CAR T cells have intrinsic stem-like properties and differentiate into memory T cell subsets but are non-protective against primary or secondary tumors. S233 cytokine armoring alone or with CD4 depletion improved effector responses but limited CAR memory T cell generation. S233-armored CAR T cells or CD4 depletion therapy induced endogenous tumor-specific TCIRC and TRM T cells, but the combination potentiated endogenous memory T cell generation and resulted in improved protection against B16F10 rechallenge.